2018
DOI: 10.1152/ajplung.00461.2017
|View full text |Cite
|
Sign up to set email alerts
|

Lumacaftor (VX-809) restores the ability of CF macrophages to phagocytose and kill Pseudomonas aeruginosa

Abstract: Cystic fibrosis (CF), the most common lethal genetic disease in Caucasians, is characterized by chronic bacterial lung infection and excessive inflammation, which lead to progressive loss of lung function and premature death. Although ivacaftor (VX-770) alone and ivacaftor in combination with lumacaftor (VX-809) improve lung function in CF patients with the Gly551Asp and del508Phe mutations, respectively, the effects of these drugs on the function of human CF macrophages are unknown. Thus studies were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
70
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 35 publications
1
70
0
Order By: Relevance
“…Ivacaftor may be acting by a CFTR-dependent mechanism, as has been described for other cystic fibrosis-related myeloid cell defects [11,12]. Ivacaftor could also act directly on monocytes by a CFTR-independent mechanism; recent studies observed that CFTR modulators may have immune-dampening effects on macrophages that lack modulator-susceptible CFTR mutations [12,13]. Finally, reduced monocyte IFN-γ responses could be a secondary effect of ivacaftor.…”
mentioning
confidence: 90%
“…Ivacaftor may be acting by a CFTR-dependent mechanism, as has been described for other cystic fibrosis-related myeloid cell defects [11,12]. Ivacaftor could also act directly on monocytes by a CFTR-independent mechanism; recent studies observed that CFTR modulators may have immune-dampening effects on macrophages that lack modulator-susceptible CFTR mutations [12,13]. Finally, reduced monocyte IFN-γ responses could be a secondary effect of ivacaftor.…”
mentioning
confidence: 90%
“…In addition to neutrophils, the beneficial effects of CFTR modulators were also demonstrated on MDMs from people with CF ex vivo. Barnaby et al studied the effects of lumacaftor alone or in combination with ivacaftor on the ability of human F508del/F508del MDMs to phagocytose and kill P aeruginosa . Lumacaftor alone restored the ability of CF MDMs to phagocytose and kill P aeruginosa to levels observed in MDMs obtained from non‐CF subjects.…”
Section: Associations Between Abnormal Cftr and Airway Inflammationmentioning
confidence: 99%
“…Although lumacaftor alone had no significant effect on P aeruginosa ‐stimulated cytokine secretion by CF MDMs, ivacaftor alone or ivacaftor in combination with lumacaftor significantly reduced secretion of several proinflammatory cytokines, including IL‐6, IL‐8, TNF‐α, IFN‐γ, and GM‐CSF. The authors speculated that the clinical efficacy of lumacaftor/ivacaftor may have been due to the ability of lumacaftor to stimulate phagocytosis and killing of P aeruginosa by macrophages . The fact that the inflammatory response in cells isolated from people with CF and studied ex vivo was attenuated by the administration of CFTR modulators indicates that CF inflammation is not entirely effective or beneficial, but it may be related to the underlying basic defect.…”
Section: Associations Between Abnormal Cftr and Airway Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the corrector VX809 does not produce an effect on proinflammatory cytokines production by macrophages exposed to P. aeruginosa while stimulating their phagocytosis activity. In contrast, the potentiator VX770 reduces proinflammatory cytokines but inhibits macrophages’ phagocytosis activity ( Barnaby et al, 2018 ). VX809 alone or in combination with VX770 does not affect pro-inflammatory cytokines production by CF airway epithelial cells.…”
Section: Cf Airway Disease Treatments and Inflammationmentioning
confidence: 99%